Frequency and Risk Factors of Acute Appendicitis in Patients with Equivocal Appendicitis - Rahim, Safwan Abdul (Indus Journal of Bioscience Research, 2025)
Objective: “To determine the frequency of acute appendicitis in patients with equivocal appendix; CT interpretation and to assess risk factors that favor acute appendicitis in patients with equivocal appendix. Study design: Cross sectional study. Study place and duration: General Surgery Department of Tertiary Care Hospital in Karachi for 6 months from 11th July 2023 to 31st December 2023. Patients and method: After meeting selection criteria 172 patients were enrolled. The patient’s data was filled using a performa, including details regarding age, gender, Neutrophil-to-lymphocyte ratio, and WBC count Using HIMS database by data collectors. The Alvarado score greater than 7 was followed with CT scan and Histopathology. All the collected data was entered and analyzed on SPSS version 20. Results: The mean age of the patients was 35.06±14.24 years, 89 (51.7%) patients were male and 83 (48.3%) were diabetics. Appendicitis was detected on CT in 80 (46.51%) patients. In patients with positive appendicitis on CT, the mean neutrophil count was 88.87±6.58, mean lymphocyte count was 14.8±3.07 and mean NLR was 6.27±1.22. In negative patients was 88.74±6.57 (p-value=0.260). In patients with positive appendicitis on CT the and in negative appendicitis on CT patients was 14.75±2.92. In negative patients mean neutrophil count was 6.22±1.17, mean lymphocyte count was 14861.07±3066.26 and mean NLR was 14751.52±2917.27. The difference in parameters was insignificant whether patients were positive or negative for acute appendicitis. Conclusion: This study concludes that the frequency of acute appendicitis in patients with equivocal appendicitis as determined by CT interpretation is 46.51% while factors include age, gender, BMI, diabetes, and raised NLR showed no association with appendicitis on CT scan.